2010
DOI: 10.1007/s12011-010-8660-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Mineral Concentrations, Biochemical and Hematological Parameters in Horses with Pica

Abstract: The aim of this study was to compare hematological, some biochemical parameters, and serum trace element concentrations in horses with or without pica. Fifteen horses with pica (group I) and another 15 healthy horses without pica (group II) were used. The hematological parameters were not changed between the two groups. In group I, hemoglobin values were lower than those of group II. However, the difference in hemoglobin values between the two groups was not significant (P > 0.05). Serum iron and copper concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 11 publications
3
14
0
2
Order By: Relevance
“…Concentrations of plasma microelements vary in domestic horses and are influenced by both the feeding ration and physiological states such as pregnancy and lactation. Table 9 shows that the concentrations of copper and zinc in the Przewalski horses are approximately in the centre of ranges measured in domestic horses by various authors (Grace et al 1999;Yur et al 2008;Aytekin et al 2010). …”
Section: Biochemistrymentioning
confidence: 71%
“…Concentrations of plasma microelements vary in domestic horses and are influenced by both the feeding ration and physiological states such as pregnancy and lactation. Table 9 shows that the concentrations of copper and zinc in the Przewalski horses are approximately in the centre of ranges measured in domestic horses by various authors (Grace et al 1999;Yur et al 2008;Aytekin et al 2010). …”
Section: Biochemistrymentioning
confidence: 71%
“…Nikvand et al (2018) determined that low serum iron concentration accompanied by low serum ferritin might be associated with long-term nutritional iron deficiency, which then plays an important role in the occurrence of pica in cattle. Similarly, Aytekin et al (2011) found that horses with pica had lower concentrations of serum iron and copper in relation to healthy horses. In another study performed on 15 lambs having pica symptoms; iron deficiency was found and it was related to the aetiology of pica in lambs (Aytekin et al 2010).…”
Section: Discussionmentioning
confidence: 88%
“…Pica or in another word "depraved appetite" has been an important subject in various animals and different aetiologies speculated to play role in the development of the problem (Meyer and Lohes 2002;Aytekin et al 2010Aytekin et al , 2011. Many factors have been identified in the aetiology of the pica in animals, therefore, pica is an interesting and very complex topic for researchers.…”
Section: Discussionmentioning
confidence: 99%
“…As an antibody activator copper plays a role in systemic immune processes. It affects the bioavailability of iron and enables its absorption (Rosen et al 1995;Aytekin et al 2011). A reduced serum concentration of copper in horses may be observed in the case of excessive concentrations of antagonistic elements, such as calcium (Vranković et al 2015).…”
Section: Discussionmentioning
confidence: 99%